Assessment for Learning: Bridging the Gap Between Instruction and Student Agency - Elen Marlez; Dev Renborw; Eka Mahargiani Rokhma; Siti Qomala Khayati; Mohammad Abdul Munjid (International Journal of Post Axial: Futuristic Teaching and Learning, 2026)
This study explores how Assessment for Learning (AfL) practices can serve as a bridge between traditional instructional methods and the cultivation of student agency in contemporary classrooms. Using a qualitative case study approach, the research investigates the ways in which formative assessment strategies—such as feedback, self-assessment, and goal-setting—transform the teacher-student dynamic and empower learners to take an active role in their learning process. Data were collected through interviews, classroom observations, and document analysis in multiple school contexts. The findings reveal that AfL not only enhances academic performance but also strengthens student motivation, metacognition, and autonomy. Teachers who embedded AfL practices into their instruction noted improved student engagement and clearer learning trajectories. However, systemic challenges such as rigid curricular standards and assessment policies hinder the full implementation of AfL. The study concludes that effective AfL requires supportive leadership, ongoing teacher professional development, and a cultural shift toward learner-centered pedagogy. These findings offer implications for educational policy, classroom practice, and teacher training programs aimed at enhancing both learning outcomes and student empowerment.